Self-esteem levels in school-going adolescents across the slums of Karachi, Pakistan: a cross-sectional analysis - Naeem, Hira; Sharif, Sana; Sharif, Hina; Seemi, Tooba (Frontiers in Child and Adolescent Psychiatry, 2023)
Introduction: For individuals to live their lives and integrate into society, self-esteem is an essential feeling. Self-esteem development depends on the environment in which children are nurtured. Assessment techniques using questionnaires include Rosenberg's self-esteem scale. Objective: The study aims to assess the self-esteem of school-going adolescents in slum areas. Methodology: This school-based cross-sectional study was conducted in three understudied slum areas of Karachi, Pakistan. A standardized scale Rosenberg Self-esteem Scale (RSES), and a pre-tested demographic scale was used to assess the impact of gender, weight, the academic performance of adolescent, tuition, and parent's education level along with parent's strictness on the self-esteem of the understudied population adolescents aged between 11-19 years were included in the study. Parent consent was obtained before visiting the school. Findings: As per the collected data on self-esteem among 539 school-going adolescents. 232 (43%) were males, and 307 (57%) were females. Most students, 324 (60%), belong to the 14-16 age range. Parents' education status and strictness towards their children, academic performance, and adolescent body mass index (BMI) influenced self-esteem levels. Conclusion: The study found that age, Parent's education, as well as parent's strictness, BMI and academic performance were linked to the level of self-esteem in the target population regardless of their gender. The children's surroundings play an imperative role in developing lower or higher self-esteem in children. Assessing children's self-esteem can be a valuable way to develop considerate circumstances and is beneficial to treatment for children with psychosomatic complaints.